Field epidemiology training programs contribute to COVID-19 preparedness and response globally - Audrey E. Hu; Robert Fontaine; Reina Turcios-Ruiz; Aisha A. Abedi; Seymour Williams; Angela Hilmers; Eni Njoh; Elizabeth Bell; Carl Reddy; Kashef Ijaz; Henry C. Baggett (BMC, 2022)
Abstract Background Field epidemiology training programs (FETPs) have trained field epidemiologists who strengthen global capacities for surveillance and response to public health threats. We describe how FETP residents and graduates have contributed to COVID-19 preparedness and response globally. Methods We conducted a cross-sectional survey of FETPs between March 13 and April 15, 2020 to understand how FETP residents or graduates were contributing to COVID-19 response activities. The survey tool was structured around the eight Pillars of the World Health Organization's (WHO) Strategic Preparedness and Response Plan for COVID-19. We used descriptive statistics to summarize quantitative results and content analysis for qualitative data. Results Among 88 invited programs, 65 (74%) responded and indicated that FETP residents and graduates have engaged in the COVID-19 response across all six WHO regions. Response efforts focused on country-level coordination (98%), surveillance, rapid response teams, case investigations (97%), activities at points of entry (92%), and risk communication and community engagement (82%). Descriptions of FETP contributions to COVID-19 preparedness and response are categorized into seven main themes: conducting epidemiological activities, managing logistics and coordination, leading risk communication efforts, providing guidance, supporting surveillance activities, training and developing the workforce, and holding leadership positions. Conclusions Our findings demonstrate the value of FETPs in responding to public health threats like COVID-19. This program provides critical assistance to countries' COVID-19 response efforts but also enhances epidemiologic workforce capacity, public health emergency infrastructure and helps ensure global health security as prescribed in the WHO's International Health Regulations.